PEMANFAATAN WARISAN KEDATUAN SRIWIJAYA SEBAGAI SUMBER PEMBELAJARAN - Susanti, Retno (Balai Arkeologi Sumatera Selatan, 2019)
Sriwijaya Kadatuan founded by Dapunta Hiyang Sri Janayasa in 682 had been widely developed and later became as one the famous maritime kingdom in the history. Most of the people lived from sailing and trading. This fact was closely related to the availability of ample natural resources they used for trading commodities. Sumatra had been a well- known place for trading goods based on forest and mining products, as well as other natural resources. Having these wealthy commodities, many foreigners from overseas countries such as Arab, Persian, Indian, and Chinese, had been deliberately come to visit Sriwijaya for trading. The existence of Sriwijaya in Sumatera along with its rich natural resources and its vital position in regional trading had triggered the place turn out into the prominent kingdom. During 8-12 century, this kedatuan had controlled over Melaka strait; a main sailing and trading channels during the period. Moreover, Kadatuan Sriwijaya presumably had taken control over the western sea of archipelago. Although the existence of Sriwijaya have been widely known, in actual fact, most of the people have not yet well informed about its preeminence in the past. This is because a number of valuable information still tied up. The similar circumstances in educational setting, inadequate information about Sriwijaya have an effect on the childrens understanding and perception on glorious and great values of our nation in the past. Even if there were some accessible information, but they were only scrappy and extraneous historiographies. As the consequences, a number of important aspects for the historical information have faded away that brought about barriers to the children in appreciating the historical inheritances from the past. Considering the important of recognizing the historical inheritances for our national living, there should be an adequate knowledge and understanding on the historical inheritance to be passed on to children since the early beginning. So, the utilization of historical inheritance as the learning resources in education becomes a need and a necessity. Therefore, the process for digging great values from the past prominent could be used in more appropriate and meaningful for the purpose of nowadays and future needs.